Concept of Profit Sharing for the Management of Village Fund Grants Perspective of DSN MUI Fatwa No/114/DSN-MUI/IX/2017 (Case Study of the Kartini Farmer Group, Hanna Plantation Village, Kualuh Hulu District, North Labuhanbatu Regency) - Hanzana Puja; Abd. Rahman Harahap (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The community carries out forms of cooperation, one of which is in the field of animal husbandry, which uses a syirkah contract with the Abdan syirkah type in Hanna Plantation Village, a farmer group manages Village fund grants to become a duck farm using an oral agreement, a clear agreement is needed so that there are no disputes in the future. This research aims to find out the concept of profit sharing from Village fund grants to the Kartini farmer group from the perspective of DSN MUI Fatwa No/114/DSN-MUI/IX/2017 in Hanna Plantation Village, Kualuh Hulu District, North Labuhanbatu. The type of research used in this research is empirical legal research using a sociological juridical approach, collecting data utilizing observation and interviews. The results of this research show that the concept of profit sharing in farmer groups for Village grant funds does not follow the verbal agreement that has been made, such as the agreement on the results of duck farming which must provide a portion for electricity payments to both members because duck care activities are carried out between two members of the group.